Faktor-Faktor yang Mempengaruhi Penyerapan Anggaran Pada Satuan Kerja Badan Layanan Umum Universitas Jambi - Dwiana Suharti IH; Achmad Hizazi; Ilham Wahyudi (Magister Ilmu Akuntansi Universitas Jambi, 2023)
This study aims to determine the effect of budget planning, human resources, procurement of goods/services, administration, organizational commitment, and budgeting participation on budget absorption in the work unit of the Jambi University Public Service Board. This research is a quantitative research with an explanatory survey method and uses data from a questionnaire. The population and sample of this research are the Proxy of Budget Users (Rector), Deputy Chancellor for General Affairs and Finance, Head of General Affairs, Planning and Finance Bureau, Deputy Dean for General Affairs, Planning and Finance at the Faculty and Postgraduate, BUPK Finance Coordinator, Finance Coordinator, and Financial Managers (PPK, BP, BPP, PPK Staff, and Finance Staff) at Jambi University as many as 76 people. There were 73 questionnaires that were returned and could be processed. The data analysis method used in this study was multiple regression analysis with the help of SPSS 24.0 for Windows. The results show that budget planning, human resources, procurement of goods/services, administration, organizational commitment, and participation in budgeting have a positive effect on budget absorption in the Jambi University Public Service Agency work unit. Budget planning and participation in budgeting have a significant effect on budget absorption in the Jambi University Public Service Agency work unit. Human resources, procurement of goods/services, administration, organizational commitment have no significant effect on budget absorption in the Jambi University Public Service Agency work unit.